Role Model Based Character Education Management in Elementary Schools: A Case Study of SDN Kalideres 01 Pagi and SDIT Adzkia - Sri Mulyani; Iim Wasliman (Journal of Science and Education (JSE), 2025)
This study examines the strategic role of role-model–based management in character education to strengthen commendable conduct among fifth-grade elementary students. Using a qualitative case study approach, the research was conducted at SDN Kalideres 01 Pagi (West Jakarta) and SDIT Adzkia (Tangerang Regency), involving principals and homeroom teachers actively managing character programs. Data were collected through in-depth interviews, participant observation, and document analysis (teaching modules, program calendars, behavior journals/portfolios), and analyzed using the Miles, Huberman, and Saldaña interactive model (data reduction, data display, conclusion drawing/verification). Findings indicate that role-model–based character education when planned collaboratively, organized through distributed roles, implemented consistently in classroom routines and school culture, and monitored via formative assessment (portfolios, journals, reflection) significantly supports the internalization of core values (discipline, responsibility, honesty, care). The planning stage maps priority values and cross-subject behavioral indicators; organizing clarifies the roles of principals, teachers, and parents; implementation emphasizes habituation and authentic modeling; monitoring combines daily records, constructive feedback, and school–family partnerships. The study concludes that role-model–centered character management, underpinned by instructional leadership and a collaborative culture, can move character from slogans to habits and should be integrated into elementary school management systems.